The Influence Of Service Quality On Passenger Satisfaction And Loyalty In Airasia Airlines - Bait, Jennifer Farihatul; , Ihwan Susila, SE., M.Si., Ph.D (2017)
The objective of this study is to examine the influence of passengers' perceived service quality on passengers' satisfaction and loyalty in the context of AirAsia Airlines as a low cost carrier airlines company. To achieve this objective, the research elaborates three specific objectives. The data was collected using fully-structured questionnaires. Non probability sampling technique with purposive sampling technique was used to collect the data and it covered 120 respondents. The statistical package for social sciences (SPSS 16.0) was used to analyze the data. To test the hypothesis, path analysis was performed. The result indicated that passengers perceived service quality to have a significant influence on both satisfaction and loyalty. It is recommended that AirAsia should consider implementing various strategies for improving service quality, especially in-flight entertainment and a more accessible and informative web site and also improving the attitude towards passangers of the delayed flight. Tujuan dari penelitian ini adalah untuk menguji pengaruh kualitas pelayanan terhadap kepuasan dan loyalitas pelanggan dalam AirAsia Airlines Sebagai perusahaan penerbangan low cost carrier. Untuk mencapai tujuan ini, penelitian menguraikan tiga tujuan. Data dikumpulkan dengan menggunakan kuesioner. teknik pengambilan sampel yang digunakan adalah non probability sampling dengan purposive sampling dan mengambil 120 responden. Dalam penelitian ini SPSS 16.0 digunakan untuk menganalisis data. pengujian hipotesis menggunakan analisis jalur (path analysis). Hasil penelitian menunjukkan bahwa kualitas pelayanan memiliki pengaruh yang signifikan terhadap kepuasan dan loyalitas. AirAsia harus mempertimbangkan untuk menerapkan berbagai strategi untuk meningkatkan kualitas layanan, terutama hiburan dalam penerbangan dan menyediakan situs web yang lebih mudah diakses dan informatif dan juga meningkatkan Sikap terhadap penumpang penerbangan yang tertunda.